2014
DOI: 10.1242/dev.106658
|View full text |Cite
|
Sign up to set email alerts
|

The splicing factor PQBP1 regulates mesodermal and neural development through FGF signaling

Abstract: Alternative splicing of pre-mRNAs is an important means of regulating developmental processes, yet the molecular mechanisms governing alternative splicing in embryonic contexts are just beginning to emerge. Polyglutamine-binding protein 1 (PQBP1) is an RNAsplicing factor that, when mutated, in humans causes Renpenning syndrome, an X-linked intellectual disability disease characterized by severe cognitive impairment, but also by physical defects that suggest PQBP1 has broader functions in embryonic development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…TALENs and CRISPR-Cas can be used in a variety of ways in Xenopus to modify specific protein domains, rearrange chromosomal organization, or to introduce the equivalent human point mutations identified through genome-wide association studies (GWAS). In addition, unbiased studies of organ formation and function in Xenopus have been shown to reveal phenotypes similar to those observed in human diseases (Iwasaki and Thomsen, 2014; Pearl et al, 2011; Sojka et al, 2014); thus, the generation of new mutants via genome editing may lead to the identification of new disease candidates. Therefore, the genome-edited Xenopus model will be instrumental as an initial tool for understanding the components and pathways affected by genetic disorders in a highly conserved vertebrate in vivo environment, which is not yet achievable with primary cell cultures or mammalian models.…”
Section: Discussionmentioning
confidence: 99%
“…TALENs and CRISPR-Cas can be used in a variety of ways in Xenopus to modify specific protein domains, rearrange chromosomal organization, or to introduce the equivalent human point mutations identified through genome-wide association studies (GWAS). In addition, unbiased studies of organ formation and function in Xenopus have been shown to reveal phenotypes similar to those observed in human diseases (Iwasaki and Thomsen, 2014; Pearl et al, 2011; Sojka et al, 2014); thus, the generation of new mutants via genome editing may lead to the identification of new disease candidates. Therefore, the genome-edited Xenopus model will be instrumental as an initial tool for understanding the components and pathways affected by genetic disorders in a highly conserved vertebrate in vivo environment, which is not yet achievable with primary cell cultures or mammalian models.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, PQBP-1 binds to the phosphorylated C-terminal domain (CTD) of RNA polymerase II (pol II), which is a platform with which many transcription regulatory proteins interact (Egloff and Murphy, 2008;Okazawa et al, 2002;Waragai et al, 1999). PQBP-1 also interacts with many components of the splicing machinery (Iwasaki and Thomsen, 2014;Mizuguchi et al, 2014;Wang et al, 2013;Waragai et al, 2000). The presence of PQBP-1 in RNA granules and early spliceosome further confirms its critical roles in pre-mRNA processing and transportation (Kunde et al, 2011;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…PQBP1 also forms complexes with mRNA‐binding proteins, including fragile X mental retardation protein (Wan, Zhang, Zhang, Li, & Han, ). In the development of Xenopus embryos, PQBP1 is expressed in mesodermal and neural tissues where it is required for normal gene expression patterning, gastrulation and neurulation (Iwasaki & Thomsen, ). Thus, the regulatory activity of PQBP1 is believed to be necessary for normal central nervous system development.…”
Section: Introductionmentioning
confidence: 99%
“…in mesodermal and neural tissues where it is required for normal gene expression patterning, gastrulation and neurulation (Iwasaki & Thomsen, 2014). Thus, the regulatory activity of PQBP1 is believed to be necessary for normal central nervous system development.…”
mentioning
confidence: 99%